Mahasiswa, HMI, dan Wirausaha - Sri Jatmiko, Tutug; Soffiatun, Soffi (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This workshop, themed "Students, HMI, and Entrepreneurship," serves as a bridge to equip HMI cadres and students in general with the mindset, strategies, and practical steps for starting a business. The goal is to encourage the emergence of young entrepreneurs who are highly integrated, capable of capitalizing on opportunities in the digital era, and ready to make a real contribution to advancing the nation's economy, in line with the identity of HMI as an organization of struggle. Through this event, it is expected that a supportive ecosystem will be created for the development of startups and businesses driven by the campus generation. The objective of the workshop, which will be attended by 60-70 new students from various departments at the State University of Malang (Universitas Negeri Malang - UM), is to produce HMI KORKOM UM cadres as entrepreneurs (both male and female) who collaborate with successful seniors. The workshop will be held at the Graha Insan Cita Building in Malang City and the Ratimaya Villa in Batu City, East Java, from October 24 to 26, 2025. The discussions will cover various issues related to politics, Islamic and National Identity, and specifically address the topic of Gen-Z Entrepreneurs in the Gig Economy Era. Keywords : Students, HMI, Entrepreneurship.